KORELASI PENDAPATAN DENGAN BADAN ANAK BARU MASUK SEKOLAH (TBABS) - Elfindri Elfindri; Djamaluddin Ancok; Syahruddin Syahruddin; Yusrizal Yuhus (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1993)
This study investigare the relationship between household economic variables with standariized height-for-age of early school children in two rural setting and one urban areas in West Sumatera. Height of 474 earlier school children were masures and mothers were interviewed. The study confirms positive relationship between household economic variables with child height with different degree of significant. The Evidence also support that height-for-age of earlier school children can be viewed as nutritional outcome as well as development achivement.